2016
DOI: 10.3390/molecules21040507
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of an Optimized Wet Milling Technology on the Crystallinity, Morphology and Dissolution Properties of Micro- and Nanonized Meloxicam

Abstract: This article reports on the effects of a new combined wet milling technique on the physicochemical properties of meloxicam (MEL). The influence of milling time on the particle size, the crystallinity, the morphology and the dissolution rate of MEL has been studied in the presence and absence of polyvinyl alcohol (PVA) as a stabilizer agent. Micronized MEL particles were produced in aqueous medium which did not contain additive after milling for 10 min. For nanonization an additive and longer milling time were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
28
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 23 publications
2
28
1
1
Order By: Relevance
“…The crystal structure of meloxicam didn't change during the ablation process, and only a slight decrease in the crystalline fraction was observed. The amorphization of meloxicam could also increase the dissolution rate and improve the bioavailability of the poorly water soluble drug (especially if accessing the nanometer size range as well) [55].…”
Section: Resultsmentioning
confidence: 99%
“…The crystal structure of meloxicam didn't change during the ablation process, and only a slight decrease in the crystalline fraction was observed. The amorphization of meloxicam could also increase the dissolution rate and improve the bioavailability of the poorly water soluble drug (especially if accessing the nanometer size range as well) [55].…”
Section: Resultsmentioning
confidence: 99%
“…The drug compounds (active pharmaceutical ingredients, APIs) included in nanosuspensions can exist in crystalline or amorphous forms. The produced liquid pre-dispersion can be converted into intermediate solid products, such as powder, by means of drying or into a semi-solid formulation,such as gel (Bartos et al, 2016;Hao et al, 2015;Lindfors et al, 2007;Rabinow, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…This study was performed using 2.5% PVA solution. 23 The ratio of the concentrated predispersion (2.0 g of Mel+18.0 g of PVA aqueous solution) and pearl amount was different: 1:0.5, 1:1, 1:2, and 1:4 (w/w). It can be established that the pearl amount and the milling time have a great effect of on the d (0.5) value ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…In our earlier studies, we investigated the applicability of the combined wet milling technique, 20 23 and these preliminary studies showed that for the nanonization of Mel, PVA as a stabilizer agent and an increased milling time (>50 min) were required. The influence of milling time was also studied on the particle size distribution, crystallinity, and dissolution rate of Mel.…”
Section: Introductionmentioning
confidence: 99%